NMR-SSC magnetic field profiler applied to magnetic field shimming - Segnorile, Hector Hugo (2013)
A new methodology aimed to control the spatial dependence of a magnetic field within a volume of interest is described. The designed hardware uses Nuclear Magnetic Resonance (NMR) to sense the magnetic field. A modified version of the Statistical Signal Characterization (SSC) method was used to analyze the NMR signal, providing a dynamical definition of the characterization parameters. The information is used to control the currents driving a set of coils that introduce corrections in the spatial dependence of the main field generated by an independent unit (magnet or electromagnet). As a practical matter, we deal with the particular case of magnetic field shimming.